Evolution of mammary prostheses and the incision methods used in adhesive mamoplasty procedures - Lays Lopes Monteiro; Wagner Mangiavacchi; Dayara Gomes Machado (Revista Brasileira de Cirurgia Plástica)
The study aims to analyze articles already published in breast augmentation, to analyze the various procedural techniques used for the placement of breast prostheses, highlighting their disadvantages and advantages, types and evolution of prostheses. The choice of prosthesis and the type of Surgical incisions are very important decisions that must be taken together (doctor and patient), taking into account the advantages and disadvantages of each incision. A good clinical preoperative explanation is essential to determine the goals to be achieved, thus avoiding possible repair surgeries or replacement of the size of the prosthesis. The enhancement of external beauty has gained more and more space, proof of which is the increasingly crowded plastic surgeons’ offices. The USA is the champion country in plastic surgery, followed by Brazil. Augmentation mammoplasty is the second most performed surgery worldwide, second only to liposuction. People seek this method as an alternative to improve self-esteem or to try to fit into a “fictitious” beauty standard established by society. The present work has a study methodology of the narrative bibliographic review type. The instrument used was a literature review and a comparative method between articles published in plastic surgery, focusing on breast augmentation based on the inductive method. The study was based on international and national articles, using SciELO and The Lancet as research sources.